Peran Case Manager dalam Mendukung Patient Centered Care di Rumah Sakit Umum Daerah Tobelo Study Henomenology Eksploratif - Mailoa, Christian; Dedi, Blacius; Trihapsari, Shindi (Syntax Literate, 2023)
The current patient service paradigm is patient- focused services (Patient Centered Care). Patients and families need accurate information, so caregiver professionals (PPAs) are required to work in an integrated manner in providing services to patients. The problem arises from the many conflicts between interdisciplinary service providers, plus the lack of quality control and control which is a serious problem for hospitals. Case Manager is an important and comprehensive intervention in order to improve quality, cost control, patient safety, integrated care, continuity of service and patient satisfaction. The role of Case Manager is very important and very complex as part of implementing patient-focused services, playing a role in helping to improve interprofessional collaboration and being able to collaborate with other health care teams. of this study was to describe the role of Case Manager and its implementation in supporting Patient Center Care at the hospital. Type of research qualitative with Phenomenological Approach with Main Informant Case Manager and Service Supervisor 27 Informants, data were obtained through in-depth interviews and Focus Group Discussion (FGD). This research identified six main themes: (1) Qualifications and Competencies; (2) SOP for Task Implementation; (3) Document Completeness; (4) Reporting System; (5) Integrated Services; (6) Obstacles to the Implementation of Duties. The role of Case Manager and Implementation at Tobelo Regional Hospital has supported Patient Centered Care and the dominant role is the role of communication and the role of coordination